Легенды и мифы Древней Греции - Кун Николай Альбертович (ЭКСМО, 2016)
Экземпляры: ф.13 (20210813) / Инвентарный номер: 59114 / Цена: 100.00 / Сис.шифр: 82.3(0)32 / Авт.знак: К 91 / ГРНТИ: 17.82.93 / ББК: 82.3(0){321},44-0-181;я93